2016
DOI: 10.1038/srep19942
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the biological effects of acupuncture treatment modulating multiple metabolism pathways

Abstract: Acupuncture is an alternative therapy that is widely used to treat various diseases. However, detailed biological interpretation of the acupuncture stimulations is limited. We here used metabolomics and proteomics technology, thereby identifying the serum small molecular metabolites into the effect and mechanism pathways of standardized acupuncture treatments at ‘Zusanli’ acupoint which was the most often used acupoint in previous reports. Comprehensive overview of serum metabolic profiles during acupuncture s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…As an important part of systemic biology, metabolomics is a front subject in the field of medical research272829. It can represent the pathophysiological changes of integrated living systems which are caused by endogenous or exogenous factors303132. Because the chemical compositions of herbal medicine are complicated, scientific research could not always reveal the effective constituents and the mechanisms of action of traditional medicine.…”
mentioning
confidence: 99%
“…As an important part of systemic biology, metabolomics is a front subject in the field of medical research272829. It can represent the pathophysiological changes of integrated living systems which are caused by endogenous or exogenous factors303132. Because the chemical compositions of herbal medicine are complicated, scientific research could not always reveal the effective constituents and the mechanisms of action of traditional medicine.…”
mentioning
confidence: 99%
“…Although the exact mechanisms of acupuncture are currently unknown, it is likely that the nervous system, neurotransmitters, and endogenous substances are involved in needle stimulation. 16 Annexin A1, an endogenous anti-inflammatory molecule described as a repressor of the innate immune response, 17 is a calcium-binding protein that promotes phagocyte migration and infiltration of granulocytes at wound sites and acts as an antimicrobial agent. 18 Annexin A1 is upregulated under pathological conditions, such as in multiple sclerosis and hypoxic-ischemic brain damage.…”
mentioning
confidence: 99%
“…[60][61][62][63][64][65][66][67][68][69][70][71] It can monitor small molecule metabolites changes in biological samples. [72][73][74][75][76][77][78][79][80][81][82][83] In this study, we used the untargeted metabolomics technology to discover the metabolic pathways and biomarkers to reveal the potential biological mechanism of syringin on the hepatitis B virus. The immunohistochemistry results showed that monocytes inltrated the histopathological analysis and were present in the liver of mice, which was consistent with the pathological changes occurring with chronic hepatitis B.…”
Section: Discussionmentioning
confidence: 99%